MRI Findings in Encephalopathy with Primary Carnitine Deficiency: A Case Report. Issue 2 (10th March 2014) - Yilmaz, Temel Fatih; Atay, Musa; Toprak, Huseyin; Guler, Serhat; Aralasmak, Ayse; Alkan, Alpay
ABSTRACT: BACKGROUND AND PURPOSE: We presented MRI and DWI findings of a 12‐year‐old boy with primary carnitine deficiency, manifested with hypoglycemic hypoketotic encephalopathy. METHODS: Magnetic resonance imaging (MRI) and diffusion weighted imaging (DWI) were performed to the patient. RESULTS: In our case, T2 hyperintensity and diffusion restriction were noted bilaterally in the corona radiate, cerebral white matter, deep white matter of cerebellum, ascending (inferior cerebellar peduncle) and descending tracts (corticospinal and corticobulbar tracts) of brainstem. CONCLUSIONS: MRI and DWI are helpful in the diagnosis, therapy planning and follow up of encephalopathic cases with carnitine deficiency.